Effects of zinc supplementation on nutritional status and cognition in children - Retno Asih S; Endang Warsiki; Boerhan Hidajat (Indonesian Pediatric Society, 2006)
Background Zinc deficiency is common in children in develop-ing countries and data suggests the effects are detrimental towardschildren’s growth and neuropsychologic performance. Results ofmultiple studies which assess these effects have been inconsis-tent.Objective To evaluate the effects of zinc supplementation onnutritional status and cognition in children with zinc deficiency.Methods Forty-six stunted children aged 50-80 months with lowhair zinc levels were randomly assigned to receive either 7.5 mgelemental Zn or placebo twice a week for 3 months. Anthropom-etry and cognition were assessed at the beginning and the end ofthe supplementation period. Differences among both groups foranthropometry and cognition before and after supplementation wereanalyzed with paired t-test. A comparison of different anthropom-etry and cognition among the two groups were analyzed using theindependent t-test.Results There were no significant differences among baselinecharacteristics except on sex distribution.There was a significantdifference in weight for age between the zinc group and placebo[0.28 (SB 0.18) vs 0.09 (SB 0.14); P=0.0001]. Height incrementswere also greater in the zinc group [0.34 (SB 0.15) vs 0.02 (SB0.12); P=0.0001). There was no significant difference betweenweight for height. Intelligence quotient (IQ) measured by theStanford-Binnet test was slightly higher in the zinc group [2.26 (SB3.11) vs 2.00 (SB 2.81], but the difference was not significant ac-cording to sex.Conclusion Zinc supplementation produced highly positive re-sponses in weight for age and height for age increments in chil-dren with zinc deficiency compared with placebo. There was noeffect of zinc supplementation on weight for height index and noneon cognition measured by intelligence quotient (IQ)